2015
DOI: 10.4314/ahs.v15i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Tackling sexually transmitted infection burden in Ugandan communities living in the United Kingdom: a qualitative analysis of the socio-cultural interpretation of disease and condom use

Abstract: Background: Despite being in a different country and social environment, Ugandans living in the UK still reportedly have the lowest rates of condom usage and one of the highest incidences of STIs in UK. In Uganda, STIs and HIV prevalence has been reported to be on the increase. Understanding peoples' beliefs and the attitudes that influence their behavior is a key factor to effectively designing control programs. Methods: A qualitative study that interviewed 37 purposively selected Ugandans living in the UK wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…We found low syphilis testing rates among HMSW and FSW which is consistent with prior studies of sex workers in Uganda, and elsewhere, that reported low syphilis testing behaviors [3,20,30,47,48]. Syphilis is a less stigmatized disease than HIV in Uganda [49]. One study found that the perception of syphilis as a genetic (inherited) disease was a barrier to testing among men [50].…”
Section: Discussionsupporting
confidence: 88%
“…We found low syphilis testing rates among HMSW and FSW which is consistent with prior studies of sex workers in Uganda, and elsewhere, that reported low syphilis testing behaviors [3,20,30,47,48]. Syphilis is a less stigmatized disease than HIV in Uganda [49]. One study found that the perception of syphilis as a genetic (inherited) disease was a barrier to testing among men [50].…”
Section: Discussionsupporting
confidence: 88%
“…We found low uptake of recent syphilis testing which is consistent with prior studies of sex workers in Uganda, and elsewhere, that reported low syphilis testing behaviors (2,3,15,27,40). Syphilis is a less stigmatized disease than HIV in Uganda (41). One study found that the perception of syphilis as a genetic (inherited) disease was a barrier to testing among men (42).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, many aspects relate to the health and disease process. There is a pragmatic identification and orientation about these aspects, since they guide the way society and management behave in the context of health, directly affecting those individuals most affected 36,37 .…”
Section: The Influence Of Sociocultural Aspects In the Construction Omentioning
confidence: 99%